Analysis of the Relationship between Snake Fruits Sidempuan (Salacca sumatrana Becc.) and Riring (Salacca zalacca var. amboinensis) using the Morphological Characterization Approach - Matatula, Erfina Anace; Ashari, Sumeru; Soegianto, Andy (Research Journal of Life Science, 2021)
Genetic relations estimation can be used for germplasm management activities, identifying cultivars, selecting parents for crossing, and reducing the number of individual samplings in a wide range of genetic diversity. The research's fundamental purpose is to analyze kinship relationships and study the genetic diversity between the snake fruit Sidempuan plant from South Tapanuli with snake fruit Riring plants from Ambon Island. Characterization research was conducted in Padang Sidempuan, South Tapanuli, and Riring Village, Ambon Island, using Radford characterization guidelines. The morphological characterization results showed that the Sidempuan and Riring bark's ecotypes were divided into 3 main clusters and had a kinship relationship with the value of genetic similarity of 85% -100%. Even though it has similarities, there were several distinguishing characters, namely the color of the upper surface of the leaf, the folding of the edges of the leaf blade, the taste of the flesh of the fruit, the height of the plant, and the category of snake fruit flowers. In a nutshell, although they looked similar, the two ecotypes were not identical.